Hospitalisation for depressive disorder following unemployment—differentials by gender and immigrant status: a population-based cohort study in Sweden. Issue 10 (18th July 2013) - Hollander, Anna-Clara; Bruce, Daniel; Ekberg, Jan; Burström, Bo; Ekblad, Solvig
Abstract : Background: The association between unemployment and poor mental health in general is explained by both causation and selection. The aim was to study whether experiencing unemployment was a risk factor for hospitalisation for depressive disorder specifically, and whether gender and immigrant status modified the hypothesised risk. Methods: A register-based prospective cohort study, 2000–2006, of persons aged 18–64 with a strong connection to the Swedish labour market. Outcome : hospital admission for a depressive episode; F32 in International Classification of Diseases, 10th revision. Exposure : employment status. Explanatory variables : gender and immigrant status. Confounders: age group, education and marital status. Cox regression models were used to estimate HRs with 95% CIs. Results: The cohort comprised 3 284 896 adults, 47.5% women. An excess relative risk for hospitalisation was found among those who became unemployed (HR=1.94, 95% CI 1.85 to 2.03). Foreign-born women who experienced unemployment had the highest relative risk (HR=3.47 95% CI 3.02 to 3.98). Conclusions: Among persons with a strong connection to the labour market experiencing unemployment, is a risk factor for hospitalisation for depressive disorders. Unemployed foreign-born women had the highest relative risk compared with all Swedish born, all foreign-born men and to employed foreign-born women.